Ethical culture and admiration for practice of earnings management / Naznin Sultana Chaity ... [et al.] - Chaity, Naznin Sultana; Shafiul Islam, SM; Al Masud, Abdullah; Akhter, Parul; Hossain, Md. Alamgir (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
A country’s national culture is an important determinant of making decisions regarding ethical dilemmas. The degree of religiosity varies along with culture and religion. This study incorporated the ‘religious ethical culture’ to identify organizational perspectives on executive admirations for earnings management. A structural equation modeling was used by surveying 384 executives of top manufacturing companies of the Dhaka Stock Exchange using a self-administered questionnaire. Incorporating religious values into the theory of planned behavior, this study empirically examined the impact on executive admiration to act ethically. The results demonstrated that managers are more inclined to engage in earnings management practice when they feel positive (attitude towards behavior) about it and believe that key people support it (subjective norms). The empirical findings revealed that managers’ intrinsic qualities were the best indicators of their ethical intentions (perceived behavioral control). This result did not support the organizational religious ethical practice in direct relation to practice of earnings management. However, our findings supported the mediating role of individual managerial intention with organizational practice of religious ethical culture with the practice of earnings management. It could be said that religion has a beneficial impact on the promotion of corporate ethics culture and over earnings management practice.